Management of Pancreatic Calculi – an Experience of Ten Cases in a District Hospital (Medicine Today, 2020)
Introduction: Down syndrome (DS) is the most common congenital abnormality affecting numerous organs and is associated with an increased incidence of many cutaneous diseases. Lichen Planus (LP) is a quite uncommon disease and associated with many immunologically altered condition. DS is also a medical condition with altered immune function. So, a higher research of LP associated with DS is very important for better understanding of both the diseases and also for comprehensive medical care.Case Report: A 33 years old known patient of Down Syndrome presented with signs and symptoms of LP is reported in this study. The diagnosis of LP was confirmed by histopathological study. She revealed a treatment history of several course of topical and systemic steroid since last 2 years for treatment of LP without any satisfactory outcome. After proper counseling we prescribed her systemic Acitretin (25 mg) daily for 3 months. She was examined every month for subsequent 3 months and was observed very satisfactory result. There was no relapse within one year after discontinuation of treatment.Discussion: We describe an adult patient with Down syndrome, associated with lichen planus (LP). LP is an inflammatory muco-cutaneous disease and benign in nature. However, some varieties of LP may cause considerable discomfort and need various systemic treatment. We treated the patient with systemic Retinoid with satisfactory result.Conclusion: LP associated with DS is a rare condition. It may be treated with systemic Retinoid.Medicine Today 2020 Vol.32(1): 70-72